Al maun and climate crisis: Dynamic between Muhammadiyah and indigenous communities in 21th century - Iman Permadi; Ramadhani Jaka Samudra; Yassar Rizky Putra Utomo; Dina Marga Hidayati (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - This paper examines how far the da’wa approach within the body of Muhammadiyah can reinforce the socio-ecological activism in response to indigenous people relating to environmental protection.Method - Gathering analytical-descriptive method and Focus Group Discussion (FGD) with key informants and approaching the study case with Ian G. Barbour’s Dialogue and Integration of religion and science (1966)Result - This paper argues that there is a tendency in Muhammadiyah to employ that dialogical and cooperative paradigm when it comes to the vulnerability of inherited land of indigenous people toward land-grabbing and so on by company and government. Moreover, the “green feature” of Muhammdiyah activism becomes stronger after agrarian fiqh was produced by the fatwa and Islamic research council of the central board in 2020. Further, the weak referred to in Al Maun Theology is, in this case, not only the indigenous people but also the defenseless environment. This article also perceives that the equivalent of the da’wa cultural approach of Muhammadiyah is more ecological than the puritan character. It proposes a socio-eco-centric view as an effort to avoid a theological dispute between both Muhammadiyah and indigenous people that is mostly encountered in indigeneity settings and is inseparable from the surrounding nature. However, there will be two consequences in doing that way, of course: between conversion and conservation.Implication – This paper affirms al Maun's yet-to-be-completed and solidified transformative ecological power from the top down and vice versa. Nonetheless, a significant potential in the history of Muhammadiyah's heritage of discussion and inclusion is confirmed by the reflection of the three results above. Agrarian fiqh also contributed to a new understanding that environmental damage is linked to the mustadh’afin group's misery.Originality - This article looks at Al Maun's holistic and universal changing power still has not contributed much, especially to the field of environmental issues and indigenous peoples. However, the main agenda of this article is expected to contribute to gap the discourse.***Tujuan - Tulisan ini mengkaji sejauh mana pendekatan dakwah di tubuh Muhammadiyah dapat memperkuat aktivisme sosial-ekologis dalam merespon masyarakat adat terkait pelestarian lingkungan.Metode - Metode gathering analitis-deskriptif dan Focus Group Discussion (FGD) dengan informan kunci dan pendekatan studi kasus dengan Ian G. Barbour's Dialogue and Integration of religion and science (1966)Hasil - Tulisan ini berargumen bahwa ada kecenderungan Muhammadiyah menggunakan paradigma dialogis dan kooperatif tersebut dalam hal kerentanan tanah pusaka masyarakat adat terhadap perampasan tanah dan sebagainya oleh perusahaan dan pemerintah. Terlebih, “fitur hijau” aktivisme Muhammadiyah semakin kuat setelah fiqh agraria dikeluarkan oleh fatwa dan dewan penelitian Islam dewan pusat pada tahun 2020. Selanjutnya, kelemahan yang dimaksud dalam Teologi Al Maun dalam hal ini bukan hanya masyarakat adat tetapi juga lingkungan yang tak berdaya. Artikel ini juga memandang bahwa padanan pendekatan kultural dakwah Muhammadiyah lebih bersifat ekologis daripada karakter puritan. Mengusulkan pandangan sosio-ekosentris sebagai upaya untuk menghindari perselisihan teologis antara Muhammadiyah dan masyarakat adat yang banyak ditemui dalam setting adat dan tidak dapat dipisahkan dari alam sekitarnya. Namun, akan ada dua konsekuensi dalam melakukan cara itu, tentu saja: antara konversi dan konservasi.Implikasi – Makalah ini menegaskan kekuatan ekologi transformatif al Maun yang belum selesai dan dipadatkan dari atas ke bawah dan sebaliknya. Meskipun demikian, potensi yang signifikan dalam sejarah warisan diskusi dan inklusi Muhammadiyah ditegaskan oleh refleksi dari tiga hasil di atas. Fiqh agraria juga berkontribusi pada pemahaman baru bahwa kerusakan lingkungan terkait dengan kesengsaraan kelompok mustadh'afin.Orisinalitas - Artikel ini melihat kekuatan perubahan holistik dan universal Al Maun masih belum banyak berkontribusi, terutama di bidang masalah lingkungan dan masyarakat adat. Namun, agenda utama artikel ini diharapkan dapat berkontribusi pada kesenjangan wacana.